Folic acid-mesoporous silicon nanoparticles enhance the anticancer activity of the p73-activating small molecule LEM2 - Gomes Ana Sara; Correia Alexandra; Rahikkala Antti; Mäkilä Ermei; Pinto Madalena M.; Sousa Emília; Salonen Jarno; Saraiva Lucília; Santos Hélder A. (Elsevier B.V., 2022)
Many drugs with anticancer potential fail in their translation to the clinics due to problems related to pharmacokinetics. LEM2 is a new dual inhibitor of MDM2/mutp53-TAp73 interactions with interesting in vitro anticancer activity, which opens new hopes as an unconventional anticancer therapeutic strategy against cancers lacking p53 or with impaired p53 pathways. As others xanthone derivatives, LEM2 has limited aqueous solubility, posing problems to pursue in vivo assays, and therefore limiting its potential clinical translation. In this work, a mesoporous silicon (PSi)-based nanodelivery system was developed with folate functionalization (APTES-TCPSi-PEG-FA) for targeted delivery, which successfully increased LEM2 solubility when compared to bulk LEM2, evidenced in payload release study. Such effect was reflected on the increase of LEM2 cytotoxicity in HCT116 and MDA-MB-231 cancer cells when treated with LEM2-loaded APTES-TCPSi-PEG-FA, by reducing cell viability lower than 50% in comparison with bulk LEM2. Despite the reduced LEM2 loading degree, which still limits its application in further in vivo assays, the results obtained herein recognize PSi-based nanodelivery systems as a promising strategy to improve LEM2 anticancer activity and bioavailability, which will be relevant for the potential use of this potent TAp73 activator in anticancer therapy.